Experimental and theoretical study of optical properties and quantum size phenomena in the BiVO4/TiO2 nanostructures. (July 2015) - Zalfani, M.; Mahdouani, M.; Bourguiga, R.; Su, B.L.
Graphical abstract: Highlights: Novel visible-light driven photocatalysts BiVO4 /3DOM TiO2 were synthesized via hydrothermal method. Low photoluminescence intensity indicating low electron–hole recombination rate. The optical and dielectric properties of BiVO4 QDs are greatly dependent on the size. The radiative lifetime is significantly enhanced with decreasing BiVO4 QDs size. Abstract: Novel BiVO4 /3DOM TiO2 nanostructure has been synthesized by hydrothermal method. BiVO4 nanoparticles and TiO2 inverse opal structure have also been prepared as reference. The prepared samples were characterized by Diffuse reflectance UV–Visible and photoluminescence (PL) spectroscopy. The absorption spectra of BiVO4 /TiO2 nanocomposite samples show an absorption edge in the visible region, suggesting the potential application of this composite as an active visible-light driven photocatalysts. Theoretically quantum confinement phenomena and size dependent optical properties of BiVO4 quantum dots have been also studied. Using the effective mass approximation model, we computed the optical properties for spherical BiVO4 nanoparticles incorporated in TiO2 matrix. The size dependent of charge carrier's energies were calculated. The result shows that the confinement energy decreases with increase the size of BiVO4 nanoparticles. Dielectric properties of the BiVO4 nanoparticles were investigated and it was found that the dielectric constant decreases significantly as the size is reduced as a result the exciton energy decreases. It has been also found that the radiative recombination lifetime is concurrently enhanced with decreasing BiVO4 QDs size.